STUDI HISTOKIMIA PENYEBARAN LEKTIN MUCUS PADA BERBAGAI JARINGAN TILAPIA (Oreochromis mossambicus) - Cahyono Purbomartono; Akihiro Takemura; Kazunori Takano (Universitas Gadjah Mada, 2007)
The aim of this research was to know the distribution pattern of mucus lectin from the different tissue of tilapia (Oreochromis mossambicus). The samples were taken from the epithelium of buccal cavity, gills, esophagus and skin of tilapia with standard body length (SL) 15.2-25.0 cm and body weight (BW) 145-250 g. Histochemical slides were observed under fluorescent microscope. The results showed that tilapia had four kinds of different lectin, such as wheat germ agglutinin (WGA), peanut aglutinin (PNA) and dolichos biflorus (DBA). Wheat germ agglutinin lectin was present in the epithelium of buccal cavity, gill, esophagus and skin. Staining intensity of WGA mucus lectin was strong in the epithelium of buccal cavity, gill, esophagus and skin. While the PNA was present in the epithelium of buccal cavity and esophagus, and DBA lectin was only present in the esophagus. The intensity of staining of PNA was weak, both in the epithelium of buccal cavity and esophagus, same with DBA lectin which was found in the esophagus.